Standards and standardization : concepts, methodologies, tools, and applications - Information Resources Management Association (Hershey, PA : Information Science Reference, 2015)
'This reference addresses the necessity of a common system of measurement in all technical communications and endeavors, in addition to the need for common rules and guidelines for regulating such enterprises'--
Includes bibliographical references and index.
Keywords: Standardization; Information technology -- Standards; Communication of technical information